Long-term reversal of diabetes by subcutaneous transplantation of pancreatic islet cells and adipose-derived stem cell sheet using surface-immobilized heparin and engineered collagen scaffold - Song Cheol Kim (BMJ Open Diabetes Research & Care, 2020)
Objective Esterified collagen (EC) can be functionalized with heparin to enhance islet graft stability. Growth factors secreted by human adipose-derived stem cells (hADSCs) can bind efficiently to EC-heparin (EC-Hep), which enhances revascularization and cell protection. We investigated the therapeutic potential of a combined heparin-esterified collagen-hADSC (HCA)-islet sheet to enhance islet engraftment.Research design and methods This study was designed to assess the efficiency of using EC-Hep as a scaffold for subcutaneous islet transplantation in diabetic athymic mice. After the hADSC-cocultured islets were seeded in the EC-Hep scaffold, islet function was measured by glucose-stimulated insulin secretion test and growth factors in the culture supernatants were detected by protein array. Islet transplantation was performed in mice, and graft function and survival were monitored by measuring the blood glucose levels. β-Cell mass and vascular densities were assessed by immunohistochemistry.Results The EC-Hep composite allowed sustained release of growth factors. Secretion of growth factors and islet functionality in the HCA-islet sheet were significantly increased compared with the control groups of islets alone or combined with native collagen. In vivo, stable long-term glucose control by the graft was achieved after subcutaneous transplantation of HCA-islet sheet due to enhanced capillary network formation around the sheet.Conclusions The findings indicate the potential of the HCA-islet sheet to enhance islet revascularization and engraftment in a hADSC dose-dependent manner, following clinical islet transplantation for the treatment of diabetes mellitus.